INVESTIGACIÓN Y DESARROLLO MAYO-2011 (Investigación y Desarrollo, 2011)
Vol. 2 Núm. 3Revista Semestral INVESTIGACIÓN Y DESARROLLO Marzo 2011Volumen 2, Número 3 ISSN: 1390-5546Publicado: 2011-05-01revista.dide@uta.edu.ec